Natural history, reasons for, and impact of low/non-adherence to medications for osteoporosis in a cohort of community-dwelling older women already established on medication: a 2-year follow-up study. Issue 2 (February 2016) - Clark, E.; Gould, V.; Tobias, J.; Horne, R.
Abstract Summary Approximately 15 % of older women on oral medications for osteoporosis could be considered for alternatives including parenteral therapies. Collection of data on socio-demographic/clinical variables is unlikely to be helpful in predicting low/non-adherence. Alternative approaches are needed to identify individuals at risk of low/non-adherence. Introduction This study aims to identify individual patient reasons for stopping medications for osteoporosis, and to investigate whether this can be predicted from knowledge about socio-demographic/clinical data, or whether alternative approaches need to be used. Methods The Cohort for Skeletal Health in Bristol and Avon (COSHIBA) recruited 3200 older women from South West UK, of whom a proportion were on medications for osteoporosis at baseline. Information on self-reported adherence and reasons for low/non-adherence were collected at 6-monthly intervals over a 2-year period. Data was also collected on potential predictors of and impact of low/non-adherence. Results Two hundred thirty-three of 3200 (7.3 %) women were on medications for osteoporosis at baseline. Mean length of time on treatment prior to enrolment was 46 months. Of those on osteoporosis medications, 94.9 % were on bisphosphonates; 8.5 % reported low adherence and 21.6 % stopped their medication completely over the 2-year follow-up period. Length of time on medication at baseline did not influence rates of low/non-adherence. Reasons for low/non-adherence to bisphosphonates included side effects (53.9 %), practical reasons such as forgetting to take them (18.0 %) and beliefs about medications (20.5 %). No convincing predictors of low/non-adherence were identified. Conclusions Approximately 15 % of older women on oral medications for osteoporosis could be considered for alternatives including parenteral therapies. This has important implications for healthcare provision. Collection of data on socio-demographic/clinical variables is unlikely to be helpful in predicting low/non-adherence. Alternative approaches are needed to identify individuals at risk of low/non-adherence to osteoporosis medications.